Epistemology and Responsibility - Fabio Bacchini (Corela)
This paper emphasises that there is a deep unity underlying Pierre-Yves Raccah’s theory of argumentation, ethics, moral epistemology, general epistemology, philosophy of science and cognitive psychology. First I show that – on the background of his argumentative conception of justifications – Raccah’s moral antifoundationalism is a consequence of the importance he assigns to responsibility in ethics, and in particular to the meta-ethical requirement that we are fully responsible of the moral positions we hold and of the actions we perform in observance to them. Then I explain why his anticonventionalism, as well as his account of how humans can form higher-order effective metapreferences, play a very important role in achieving the target of safeguarding our full responsibility in the prescriptive realm. Finally, I argue that also Raccah’s general epistemology is aimed at supporting the thesis that we are morally responsible of both the scientific theories and the empirical statements we do accept as true. I show how Raccah can assign such a key role to responsibility also in the descriptive realm without abandoning empiricism.